Microsurgical Resection of Tuberculum Sellae Meningioma through Left Cranio-orbital Approach - Pojskić, Mirza; Arnautović, Kenan I. (Journal of Neurological Surgery Part B: Skull Base, 2018)
In this video clip, the authors present the resection of a tuberculum sellae meningioma with compression of the left optic nerve and a chiasm (Fig. 1) through a standard cranial orbital (CO) skull base approach.123 The key step in the tumor resection was microsurgical dissection of left and right A1 segments of the anterior cerebral artery and the anterior communicating artery and the separation of the tumor from these vascular structures. This was followed by careful separation of the meningioma from both optic nerves, the chiasm and the pituitary stalk. The final step was coagulation and resection of the tumor origin on the dura of the tuberculum sellae, devascularizing the tumor. Once this was achieved, the tumor was removed. Using this approach, an optimal surgical corridor to the sellar area was provided while minimizing the retraction of frontal and temporal lobes.The link to the video can be found at: https://youtu.be/O59Fj2dNXB0.
Keywords: tuberculum sellae meningioma; suprasellar meningioma; cranio-orbital skull base approach